Analisis Penerapan Metode Akumulasi Biaya Sebagai Alat untuk Menentukan Harga Pokok Produksi pada Usaha Upiya Karanji Gorontalo - Valentina Monoarfa; Natalia; Ni Wayan Dini Ari (ManBiz: Journal of Management and Business, 2024)
Determining the cost of production is an important thing to pay attention to because of the increasing competition between companies in producing quality products competitively in the Upiya Karanji Gorontalo Business. The aim of this research is to determine the application of the cost accumulation method as a tool for determining the cost of production using the full costing method. The research methads used to collect data are interviews, observation and documentation. The results of determining the cost of production using the full costing method are greater than the calculation of the company's cost of production, this occurs because the company does not calculate all factory overhead costs in detail, therefore it is recommended that Upiya Karanji's business calculate all overhead costs in detail and use the calculation method full costing.